2022
DOI: 10.1111/cpr.13205
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0083756 promotes intervertebral disc degeneration by sponging miR‐558 and regulating TREM1 expression

Abstract: Objectives Intervertebral disc degeneration (IVDD) is a leading cause of low back pain. Circular RNAs (circRNAs) have been demonstrated to exert vital functions in IVDD. However, the role and mechanism of hsa_circ_0083756 in the development of IVDD remain unclear. Materials and methods RT‐qPCR was performed to detect expressions of hsa_circ_0083756, miR‐558 and TREM1 in nucleus pulposus (NP) tissues and cells. CCK8 assay, flow cytometry, TUNEL assay, RT‐qPCR and WB were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“… Cheng et al (2018) found that circVMA21 can adsorb miRNA-200c, reduce the expression of its target X-linked inhibitor of apoptosis protein (XIAP), and successfully alleviate the degenerative changes of NP by injecting circVMA21 into a rat IDD model. Du et al (2022) found that the expression of circ_0083756 exhibited a significant rise in degenerative NP tissues and cells, adsorbing miRNA-558, promoting the process of IVD, and alleviating IDD in a rat model by silencing circ-83756. It should be noted that although some circRNA have different functions in regulating IVDD, the role and underlying mechanisms of circRNA in IVDD are still largely vague and require further research.…”
Section: Therapeutic Factorsmentioning
confidence: 96%
“… Cheng et al (2018) found that circVMA21 can adsorb miRNA-200c, reduce the expression of its target X-linked inhibitor of apoptosis protein (XIAP), and successfully alleviate the degenerative changes of NP by injecting circVMA21 into a rat IDD model. Du et al (2022) found that the expression of circ_0083756 exhibited a significant rise in degenerative NP tissues and cells, adsorbing miRNA-558, promoting the process of IVD, and alleviating IDD in a rat model by silencing circ-83756. It should be noted that although some circRNA have different functions in regulating IVDD, the role and underlying mechanisms of circRNA in IVDD are still largely vague and require further research.…”
Section: Therapeutic Factorsmentioning
confidence: 96%
“… 7. Du et al ( Du et al, 2022 ) discovered that hsa_circ_ 0083756 expression is increased in tissues and cells with NP degeneration. In vitro functional studies showed that circ_ 0083756 knockdown promotes NP cell proliferation and ECM synthesis and inhibits the release of inflammatory factors, while gene overexpression had the opposite effect.…”
Section: Detrimental Genes In Ivdmentioning
confidence: 99%
“…To date, 25 circRNAs associated with IVDD have been reported, including 12 circRNAs that promote IVDD progression and 13 circRNAs that inhibit IVDD progression. Furthermore, 23 circRNAs are reported to be involved in the regulation of ECM metabolism, including 10 circRNAs which promote ECM catabolism (Circ_0004354 [ 63 ], circ_0040039 [ 63 ], circITCH [ 64 ], Circ_0083756 [ 65 ], Circ-FAM169A [ 66 ], circRNA_0000253 [ 67 ], circRNA TIMP2 [ 68 ], cirC_001653 [ 69 ], circRNA_104670 [ 70 ], and circ_0075062 [ 71 ]) and 12 circRNAs that promote ECM synthesis (circ_0022382 [ 72 ], circSPG21 [ 73 ], circSNHG5 [ 74 ], circPKNOX1 [ 75 ], circGLCE [ 76 ], circRNA VMA21 [ 77 ], Circ-grb10 [ 78 , 79 ], circRNA-CIDN [ 80 ], circERCC2 [ 81 ], circSEMA4B [ 82 ], circ-4099 [ 83 ], and circ-FAM169A [ 84 ]) ( Table 1 and Fig. 2 ).…”
Section: Regulatory Role Of Circrnas In Degeneration Of Nucleus Pulposusmentioning
confidence: 99%
“…In addition, circITCH acts as a sponge for miR-17–5p to derepress SOX4, thus promoting the Wnt/β-catenin signaling axis to accelerate apoptosis of NPCs, growth inhibition, and ECM degradation [ 64 ]. Furthermore, Du et al [ 65 ] showed significantly increased expression of circ_0083756 in degenerative nucleus pulposus tissues, which promoted NPCs apoptosis, growth inhibition, and ECM degradation by targeting the miR-558-TREM1 pathway. Guo et al [ 66 ] revealed that the circ-FAM169A-miR-583/BTRC signaling axis regulates the NF-κB pathway-induced IL-1β and TNF-α production and ECM degradation.…”
Section: Regulatory Role Of Circrnas In Degeneration Of Nucleus Pulposusmentioning
confidence: 99%